Free light chains of immunoglobulins in patients with systemic sclerosis: correlations with lung involvement and inflammatory milieu. Issue 7 (31st January 2018) - Bosello, Silvia; Basile, Umberto; De Lorenzis, Enrico; Gulli, Francesca; Canestrari, Giovanni; Napodano, Cecilia; Parisi, Federico; Pocino, Krizia; Di Mario, Clara; Tolusso, Barbara; Ferraccioli, Gianfranco; Gremese, Elisa
Abstract : Aim: Humoral immunity and B cells are thought to play an important role in the pathophysiology of the systemic sclerosis (SSc). The production of free light chains (FLC) of immunoglobulins is abnormally high in several pathological autoimmune conditions and reflects B cell activation. Furthermore, FLCs demonstrated different biological activities including their capability to modulate the immune system, proteolytic activity and complement cascade activation. The aims of this study are to determine the FLC levels in patients with SSc compared with healthy controls (HC) and to study their possible association with organ involvement and disease characteristics. Methods: Sixty-five patients with SSc and 20 HC were studied. Clinical and immunological inflammatory characteristics were assessed for all the patients with SSc. κ-FLC and λ-FLC, interleukin 6 (IL-6) and B cell activating factor levels were measured. Results: The mean serum κ-FLC levels and FLC ratio were significantly higher in patients with SSc compared with HC, while the serum λ-FLC levels were comparable. The levels of FLC were comparable in patients with diffuse skin disease and limited skin involvement, while κ-FLC levels were increased in patients with restrictive lung (forced vital capacity (FVC) <80%) disease (26.4±7.4 mg/L) when compared with patients with FVC ≥80% (19.6±7.3 mg/L, P=0.009). In patients with SSc, the levels of serum κ-FLC level directly correlated with the IL-6 levels (R=0.3, P=0.001) and disease activity (R=0.4, P=0.003). Conclusions: FLC levels are elevated in SSc and high levels are associated with lung involvement and with a higher degree of inflammation, supporting a possible role of B cell activation in the pathophysiology of the disease.